Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
(64^3)^(1/6)
=(64)^(3×1/6)
=(64)^(1/2)
=(8^2)^(1/2)
=(8)^(2×1/2)
=8^1
=8
8 is the correct answer of your question...
Answer:
8
Step-by-step explanation:
Remember the phrase "power to a power means to multiply the exponents"
That is, if you have a number (call it x) raised to a power (call it b), and that whole expression is raised to a power (call it c), it's the same as that number x raised to the power of the product of those two powers.
[tex](x^a)^b = x^a^b[/tex]
Here's an example showing to give some intuition behind this (and a way to derive the above formula if you forget it):
[tex]x^3 = x*x*x\\(x^3)^2 = (x*x*x)^2 = x*x*x*x*x*x = x^6[/tex]
Or more simply,
[tex](x^3)^2 = x^(^3^*^2^) = x^6[/tex]
So in this case:
[tex](64^3)^\frac{1}{6} = 64^(^3^*^\frac{1}{6}^) = 64^\frac{1}{2} = 8[/tex] (remember a number raised the to the power of 1/2 is the square root of the number; in this case, the square root of 64 is 8)
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.